2020
DOI: 10.1002/jeq2.20054
|View full text |Cite
|
Sign up to set email alerts
|

The state of phosphorus balance on 58 Virginia dairy farms

Abstract: Managing a sustainable dairy farm requires balancing phosphorus (P) imports and exports that enter and leave through the farm gate. Over the long term, P surpluses will elevate soil‐test P concentrations above crop requirements through routine land applications of manure. The objectives of this study were aimed at Virginia dairy farms (a) to determine P mass balances, (b) to define potential guidelines for a sustainable and feasible zone of operation based on P balance and P use efficiency, and (c) to assess r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…A relative constancy of P surpluses with intensification level (Fig. 3(a)) has also been reported for dairy farms in Virginia, USA; P input via manure and fertilizers decreased as soil P status increased [60] . However, in many intensive grassland-based dairy systems, both N and P surpluses increase with the intensity of dairy production [23,59,61] .…”
Section: Impacts Of the Intensification Of Dairy Productionsupporting
confidence: 66%
“…A relative constancy of P surpluses with intensification level (Fig. 3(a)) has also been reported for dairy farms in Virginia, USA; P input via manure and fertilizers decreased as soil P status increased [60] . However, in many intensive grassland-based dairy systems, both N and P surpluses increase with the intensity of dairy production [23,59,61] .…”
Section: Impacts Of the Intensification Of Dairy Productionsupporting
confidence: 66%
“…The externalization of the (in)efficiencies of feed production also contributed to a high PUE; assigning a P use efficiency coefficient to purchased feed strongly decreased overall mean farm PUE and strongly decreased the differences among FE groups in farm PUE (Table 2). A relative constancy of PUE farm has also been reported for dairy farms in Virginia, USA (Pearce and Maguire, 2020).…”
Section: Variations In Nue and Puementioning
confidence: 70%
“…Such diversity of producer behavior is real and can be substantial (Ribaudo 2015). One recent study in a portion of the Chesapeake Bay watershed showed that P mass balances on adjacent farms can vary by a factor of 10 (Pearce and Mcguire 2020). Agency funding is allocated to staff and their offices that can “get BMPs on the ground” as measured by contracts processed.…”
Section: Challenges With Agricultural Nps Incentivesmentioning
confidence: 99%